Technique training in alpine ski racing: forced movement changes by a specific device - Kröll, J.; Birklbauer, J.; Stricker, G.; Müller, E. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
A crucial point of modern methods in motor learning is a high degree of exercise variability. Especially in alpine skiing, where athletes have to compensate external variability, adequate exercises have to be offered. To fulfill these requirements, a specific training device with the possibility of different settings was developed. In the present study we analyzed the function of three settings and short time adaptation effects during a training session. A mixed training protocol (race & various device settings) was compared to a normal training session. In two of three settings runtimes were significantly higher. A repeated usage of one setting led to an adaptation in runtime (sig. faster). For partial runtimes no adaptation was found. No adaptation of the original race setup was observed after applying several variable settings. The overall force distribution between inside and outside leg was not, or only marginally, influenced by the usage of the device. Very strong effects were found in the force distribution within a leg. It can be concluded that the usage has only little impact on general movement patterns (macroscopic level), but a substantial one on microscopic level. Hence, the new device generates exactly those movement variations which are recommended for modern technique training.